Chemistry, mineralogy and distribution of selected trace-elements in the Parvadeh coals, Tabas, Iran. (15th June 2016) - Rajabzadeh, Mohammad Ali; Ghorbani, Zohreh; Keshavarzi, Behnam
Abstract: The Parvadeh Coalfield located in the south of Southern Khorasan Province, with an area of 1200 km 2 is one of the most important coal producing areas in East-Central Iran and contain low to medium volatile bituminous coal (%Ro: 0.9–1.5%). The mineralogical and geochemical data of coals with respect to element partitioning during coal dressing indicated that the main minerals of feed coals are quartz, illite, kaolinite, calcite, dolomite, and pyrite. The element contents of coal-bearing layers are higher than the Clarke of Earth. Cluster statistical analysis indicates that Si, Al, Zn, V, K, Ni and Cr principally occur in the silicates, whereas Cd, Fe, As and Co displays affinity to the sulfide phase. Molybdenum, Li, Cu and Pb mainly occur in the organic fraction of coal. The high sulfur content in coals under study was influenced by seawater during peat deposition. Pyritic sulfur is the main form of sulfur in the coals from Parvadeh. Syngenetic pyrite is present as framboids associated with macerals. The calculated removability index shows that Li, Mo, Pb and Cu are enriched in the cleaned coal and are associated with organic matter in coal. The higher degree of removal for other minor elements during mineral processing however indicates that they are associated with mineral matter in coal. The coal cleaning method in Parvadeh coal-cleaning plant not only removes mineral matter and pyritic sulfur, but also reduces the content of most inorganic elements.